Power Relations in the Stadium Stands: Strengthening Gender Equality in Indonesian Football Club Supporters - Bayu Mitra A. Kusuma; Theresia Octastefani (Sawwa: Jurnal Studi Gender, 2022)
Football competition in Indonesia is commonly perceived as male-dominated supporters. However, there is a growing trend of women supporters' groups. This study aims to analyze the hierarchical and power relations between women and men members of Brigata Curva Sud (BCS), a supporter base of PSS Sleman football club, which in 2017 was praised as the best ultra supporter in Asia. The study uses a descriptive-qualitative methodology to analyze the phenomenon. Using Michel Foucault's theory of power relations, the research findings demonstrate that BCS's manifesto is "no leader, just together," which suggests that the group does not recognize or accept the hierarchical organizational structure. Each member has equal rights and responsibilities in determining the organization's future and carrying out any decisions. Second, the power dynamic between men and women in BCS is equal. The only supreme power in the BCS that generates knowledge is an open-to-all-members deliberative forum, regardless of social class or gender.